Peningkatan Kualitas Produk Basreng Salted-Egg melalui Teknologi Nitrogen Filling Band Sealer bagi UMKM Mina Karya Mandiri - Widiyanti, Widiyanti; Sudjono, Imam; Suyetno, Agus; Riza, Fahru (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
This community service activity aims to improve the quality and competitiveness of salted basreng products at UMKM Mina Karya Mandiri by implementing the Nitrogen Filling Band Sealer (NFBS) Machine. The implementation method involves several stages, namely partner surveys, idea and information exploration, work preparation and planning, tool design, tool trials, as well as socialization, tool operational training, and mentoring. The results of the analysis show that the use of NFBS increases the shelf life of products from 1 month to 6-12 months, reduces the damage rate from 20% to 2%, and reduces the product return rate from 15% to 3%. In addition, consumer satisfaction increased from 60% to 90%, and average sales increased by 50%, from 100 units to 150 units per month. The implementation of NFBS increases profit margins by 167%, from IDR 3,000,000 to IDR 8,000,000 per month, thereby increasing the competitiveness of UMKM.